Crisis constitucional e identitaria de la Unión Europea (2009)
The starting point of this article is the hypothesis that the current crisisof the European Union, mainly regarding its constitutional integration process, has deep origins that surpasses the judicial and economic fields to establish it self in the cultural and axiological identity field, regardless of certain religious aspects. Furthermore, this article analysis the mains treams that question the need to start from an European cultural identity, such as the Post Modern European and Habermas premises, in order to conclude with some considerations regarding what may contribute to better diagnose the etiology and therapy of the actual European constitutional identity crisis.